Effect of contact time on the level of phthalates in polyethylene terephthalate-bottled water from the point of sale - Abdul Rasid, Hazira; Ungku Zainal Abidin, Ungku Fatimah; Jinap, Selamat; Omar, Syaliza; Sanny, Maimunah (Universiti Putra Malaysia Press, 2021)
The study aimed to evaluate the effect of contact time on the level of phthalates in polyethylene terephthalate (PET)-bottled water commercially available on the market. Different water types (drinking water, mineral water, and sparkling water) in PET bottles and mineral water in glass bottles were collected. Control (before bottling) and freshly produced (0-month) samples were collected at manufacturing sites. In contrast, samples at 6, 12, and 18 months of contact times were collected randomly from hypermarkets and supermarkets in Klang Valley, Malaysia. The samples were analyzed using LC-MS/MS with deuterated DEHP as the internal standard. DEHP, DMP, DEP, DnOP, and BBP were not detected in drinking, mineral, and sparkling water in both PET and glass bottles. However, DBP was detected within the range of 0.68 to 1.11 ng/mL for mineral water and 0.55 to 0.59 ng/ mL for drinking water in PET bottles. All types of phthalates, including DBP, were not detected in the control and 0-month samples. DBP was detected at 0.59 ng/mL at 6 months of contact time and 0.55 ng/mL at 12 months of contact time in PET-bottled drinking water samples; the difference, however, was not significant. It appears that contact time did not significantly affect DBP levels.